Counter-terrorism laws and freedom of expression: global perspectives - Workneh, Téwodros; Haridakis, Paul (Lexington Books, 2021)
"Counter-Terrorism Laws and Freedom of Expression: Global Perspectives offers critical insight into how counter-terrorism laws have adversely affected journalism practice, digital citizenship, privacy, surveillance, online activism, and other forms of freedom of expression"--